Mechanical Performance and Design Method of Improved Lead Shear Damper with Long Stroke - Baoshun Wang; Weiming Yan; Haoxiang He (Shock and Vibration)
The paper presents experimental study on an improved plate lead shear damper with long stroke (ILSD-LS) which is developed to meet the engineering requirements for high-rise structures with long periods subjected to the long-period earthquakes. Finite element analysis is also carried out to investigate the proposed damper. Based on the ideal rigid-plastic constitutive law of lead, a mechanical model of the ILSD-LS is established. Compared with ordinary dampers, ILSD-LS has better damping force, energy dissipation capacity, and stability according to the results of simulation and experiments. The method of calculating damping force is reasonable and accurate. In order to verify the damping effect of ILSD-LS for the structures with long periods under long-period ground motions, the nonlinear time history analysis of a typical high-rise structure with ILSD-LS is carried out. The numerical results indicate that the seismic responses of the high-rise structure with ILSD-LS are significantly reduced when subjected to long-period ground motion.